Effect of cold (14° C) vs. ice (5° C) water immersion on recovery from intermittent running exercise - Anderson, D.; Nunn, J.; Tyler, C. J. (The Journal of Strength and Conditioning Research, 2018)
The purpose was to compare 14° C (CWI14° C) and 5° C (CWI5° C) cold water immersion after intermittent running. On 3 occasions, 9 male team-sport players undertook 12 minutes of CWI14° C, CWI5° C, or nonimmersed seated recovery (CON) after 45 minutes of intermittent running exercise. Maximal cycling performance and markers of recovery were measured before and in the 0-72 hours after exercise. Peak power output (PPO) was immediately reduced after all interventions (d = 1.8). CWI5° C was more effective at restoring PPO than CWI14° C (d = 0.38) and CON (d = 0.28) 24 hours after exercise, whereas both CON (d = 0.20) and CWI5 (d = 0.37) were more effective than CWI14° C after 48 hours. Cold water immersion (CWI) was more effective than CON at restoring PPO 72 hours after exercise (d = 0.28-0.30). Mean power output (MPO) was higher in CON compared with CWI5° C (d = 0.30) and CWI14° C (d = 0.21), but there was no difference between CWI5° C and CWI14° C (d = 0.08). CWI5° C was more effective than CWI14° C for restoring MPO to baseline levels 24 hours (d = 0.28) and 72 hours (d = 0.28) after exercise; however, CON was more, or equally, effective as CWI5° C and CWI14° C throughout. Lactate and creatine kinase concentrations were unaffected. Perceived muscle soreness remained elevated in CWI5 and CON throughout but was similar to baseline in CWI14° C after 72 hours. In conclusion, repeated bouts of exercise are initially impaired after 5 and 14° C CWI, but PPO may be improved 72 hours after exercise. Cold water immersion is not recommended for acute recovery based on these data. Athletes and coaches should use the time currently allocated to CWI for more effective and alternative recovery modalities.